Implementation of Technology Enhanced Formative Assessments in 21st Century Education: A Comparative Analysis - Krishnan, Jeevanithya (International Journal of Asian Education, 2023)
Teaching methods in the 21st century are more inclined to be more creative and innovative in engaging students in the digital era. Technology tools have become pivotal in 21st-century education, where students prefer flexible learning. 21st-century learning has also become more inclusive, where students become active learners. 21st-century learning has also taken a paradigm shift in analyzing student performance. Student progress is monitored by their continuous performance in the classroom in the form of feedback-based formative assessments instead of limiting them to graded summative assessments. This paper focuses on lecturers’ views on 21st-century classrooms and their challenges in implementing 21st-century learning methods. The role of technology-assisted formative assessments has also been investigated through qualitative research conducted among selected lecturers from two departments in a private institution. Research findings proved that lecturers are much more inclined towards 21st-century learning as students and lecturers like more interactive and formative assessments, as they promote continuous learning. However, using technology tools has mixed among lecturers due to its constraints in certain boundaries. It is also found that implementing 21st-century learning in the classroom contributes to challenges for the lecturers regarding technology adaptation, time constraints, and student motivation.